Avaliação das condições bióticas e abióticas em um viveiro neotropical impactado - Capitanio, Érica Camargo Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Limnological studies in fishpond considering physical, chemical and biological characteristics are of extreme importance for the maintenance of the aquatic organisms because such variable are essential to characterize the environment as a whole, permitting to amplify the understanding of the dynamics of the system and allowing the adoption of an adequate local management, increasing the productivity and quality of the commercial activity. An overlook in the planktonic community is a fundamental tool to complete such characterization because such community is composed by sensitive organism dependents upon the quality of the water. Any alteration in such condition may reflect in changes in the abundance and diversity of present species. The main objective of this study was classify the quality of the water of a fishpond located in the Aquiculture Center of the State University of São Paulo in Jaboticabal, SP - Brazil (21°11'S e 48°18'W) in relation to the planktonic community present in the system and the Trophic Status Index. The results showed a planktonic community typical of eutrophic environment with a dominance of the genera: Thermocyclops, Brachionus, Keratella and Trichocerca (zooplankton) and Anabaena, Aphanocapsa and Microcystis (phytoplankton). The Trophic Status Index corroborated with the results found for the planktonic community, classifying all sampled points in the fishpond as eutrophic (varying from 66 to 70). It is possible to conclude that the enrichment of the water column was promoted by the continuous influx in the fishpond, in which carries a higher load of effluents from nurseries and other fishpound located upstream. Such condition becomes the limnological characteristics favorable for the potentially propagation of toxic species as Microcystis aeroginosa and Pseudanabaena catenata from the Cyanobacteria group, calling the attention for an adequate management of the local, avoiding a booming of such ...

Estudos limnológicos em viveiros de piscicultura abordando as características físicas, químicas e biológicas são de extrema importância para a manutenção dos organismos aquáticos, pois caracterizam o ambiente de maneira completa, permitem compreender a dinâmica do sistema e aplicar manejo adequado no local, aumentando a produtividade e a qualidade da piscicultura. A comunidade planctônica é uma ferramenta fundamental para esta caracterização, sendo composta por organismos sensíveis às mudanças na qualidade da água que respondem através da diversidade e abundância de espécies. O principal objetivo deste trabalho foi classificar a qualidade da água de um viveiro de piscicultura (21°11'S e 48°18'W) localizado no Centro de Aquicultura da UNESP de Jaboticabal, SP, de acordo com a comunidade planctônica presente neste ecossistema e o Índice de Estado Trófico. Os resultados mostraram uma comunidade planctônica característica de ambiente eutrófico, com dominância dos gêneros: Thermocyclops, Brachionus, Keratella e Trichocerca (zooplâncton) e Anabaena, Aphanocapsa e Microcystis (fitoplâncton). O Índice de Estado Trófico corrobora os resultados obtidos através da análise da comunidade planctônica, classificando todos os pontos amostrados no viveiro como eutróficos (variando de 66 a 70). É possível concluir que o enriquecimento da coluna d'água é promovido pelo sistema de fluxo contínuo, que traz uma elevada carga para o viveiro estudado através do efluente dos viveiros e tanques localizados à montante deste, tornando as características limnológicas propícias para o desenvolvimento de espécies de Cyanobacteria potencialmente tóxicas tais como Microcystis aeroginosa e Pseudanabaena catenata, do grupo Cyanobacteria...
Keywords: Aquicultura; Limnologia; Eutroficação; Fitoplâncton; Zooplâncton; Limnology